THE CONTENTS AND TERMINATION OF THE STATUS OF AUTHORISED USER OF INDICATIONS OF GEOGRAPHIC ORIGIN OF GOODS AND SERVICES - Božin Vlasković; Zoran Miladinović; Siniša Varga (Ekonomika Poljoprivrede (1979), 2013)
Indication of geographic origin is a specific intellectual property (IP). Specificity of that IP is mirrored to its legal protection. The IP legal protection of indications of geographic origin is, at the one side, wider than of the other intellectual properties because IP legal protection of registered indication of geographic indication is essentially featured by certain public law element. But at the other side, it is notably narrower because more than one legal entity can be authorised for commercial use of the same indication of geographic origin. Furthermore, an authorised user can not obtain a right in the application nor assign registered indication of geographic origin, since these are not a subject of commerce that is one of the most important powers comprised in all others intellectual property rights, except in collective trademarks and certification marks rights. Authors in this paper deal with legal aspects of indication of geographic origin use.